2017
DOI: 10.1159/000477453
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness is an Independent Risk Factor for Anemia After Percutaneous Native Kidney Biopsy

Abstract: Background/Aims: Bleeding is the most common complication after renal biopsy. Although numerous predictors of bleeding have been reported, it remains unclear whether arterial stiffness affects bleeding complications. Method: We performed an observational study of the renal biopsies performed in our division over an approximately 6-year period (May 2010 to May 2016). The clinical and laboratory factors were analyzed to reveal the risk factors associated with bleeding, with a focus on anemia (defined as a ≥10% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Another common complication of kidney biopsy was perinephric hematoma. Two studies were identified as influential for hematoma occurrence, each finding hematomas in over 80% of the cohort (9,10). Excluding these studies only decreased the proportion of hematomas from 11% to 8.8% (from one in nine to one in 11) and had little effect on study heterogeneity (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Another common complication of kidney biopsy was perinephric hematoma. Two studies were identified as influential for hematoma occurrence, each finding hematomas in over 80% of the cohort (9,10). Excluding these studies only decreased the proportion of hematomas from 11% to 8.8% (from one in nine to one in 11) and had little effect on study heterogeneity (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Though usually safe, kidney biopsy can be associated with serious complications. The risk of minor bleeding episodes after PKB including self-limiting gross hematuria or small hematomas that did not need any blood transfusion or intervention is in the range of 17%-33% in a large meta-analysis of 9474 kidney biopsies, whereas major complications, including hemorrhage requiring transfusion, angiographic intervention, nephrectomy, or death, have been reported in only around 2%-8% of renal biopsies (5,6) Predictors of major bleeding are the presence of coagulopathy, kidney dysfunction (serum creatinine, >2.0 mg/dL), low concentration of hemoglobin, use of a wide needle, or atherosclerosis (7,8). The current data are from the only available study in the literature, on the issue of delayed onset bleed after PKB.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the absolute level of Hb decline (g/dL) after the renal biopsy was treated as the outcome, based on a previous study [ 20 ]. The relative level of Hb decline (%) and prevalence of Hb decline ≥10% were also investigated based on previous studies [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%